2018
DOI: 10.2337/db17-0526
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Long-Noncoding RNA Transcriptome Analysis of Obese Mice Identified Lnc-Leptin, Which Regulates Leptin

Abstract: Obesity induces profound transcriptome changes in adipocytes, and recent evidence suggests that long-noncoding RNAs (lncRNAs) play key roles in this process. We performed a comprehensive transcriptome study by RNA sequencing in adipocytes isolated from interscapular brown, inguinal, and epididymal white adipose tissue in diet-induced obese mice. The analysis revealed a set of obesity-dysregulated lncRNAs, many of which exhibit dynamic changes in the fed versus fasted state, potentially serving as novel molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…To explore the role of lncRNAs in adipose tissue during obesity, Lo et al ( 72 ) examined the lncRNA expression changes in BAT, epididymal WAT, and iWAT with RNA-seq and identified a set of lncRNAs regulated in all three depots during obesity and in the fed versus fast state. One of these lncRNAs was located ∼20 kb upstream of Leptin, referred to as lnc-Leptin .…”
Section: Lncrna Regulation Of White Adipocyte Differentiation and Funmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the role of lncRNAs in adipose tissue during obesity, Lo et al ( 72 ) examined the lncRNA expression changes in BAT, epididymal WAT, and iWAT with RNA-seq and identified a set of lncRNAs regulated in all three depots during obesity and in the fed versus fast state. One of these lncRNAs was located ∼20 kb upstream of Leptin, referred to as lnc-Leptin .…”
Section: Lncrna Regulation Of White Adipocyte Differentiation and Funmentioning
confidence: 99%
“…2 ). Therefore, lnc-Leptin regulates Leptin expression by mediating the formation of enhancer–promoter interaction ( 72 ).…”
Section: Lncrna Regulation Of White Adipocyte Differentiation and Funmentioning
confidence: 99%
“…Moreover, several studies reported that members of the TGFβ(transforming growth factor β) superfamily hold distinct regulatory effects on brown adipogenesis [34,35]. In addition to the regulation of transcription levels, epigenetic regulation, including microRNA [36], lncRNA [37][38][39][40], and methylation [41,42], also play essential roles in the formation and activation of BAT [43]. Although circRNA has been rarely reported in the regulation of brown adipogenesis and functions, we believe it is also a very promising potential regulator.…”
Section: Introductionmentioning
confidence: 91%
“…Robust mouse lncRNA metabolic regulators (mLMRs), such as Lexis, Mexis, and Blnc1 [9][10][11] , have also been reported by many groups and this list continues to expand. Furthermore, several genomewide transcriptome analyses in mice have identified hundreds of potential mLMRs in key metabolic organs suggesting that mouse lncRNAs constitute an additional dimension of metabolic regulation 12,13 . If human lncRNAs exercise a similar function, studying their metabolic function could help systemically uncover novel regulatory mechanisms of human metabolism and expand our understanding of how metabolic disease is initiated and progresses.…”
Section: Introductionmentioning
confidence: 99%